Searching for Ultra-diffuse galaxies in the low-density environment around NGC 3115. Issue Volume 15:Issue S359(2020) (March 2019) - Canossa-Gosteinski, Marco; Chies-Santos, Ana L.; Furlanetto, Cristina; Freitas, Rodrigo F.; Schoenell, William
Abstract: Ultra-diffuse galaxies (UDGs) are extremely low luminosity galaxies and some of them seem to have a lack of dark matter. Therefore, they can offer important clues to better understand galaxy formation and evolution. Little is known about UDGs in less dense environments, as most of the known UDGs have been found in very dense regions, in the outskirts of massive galaxies in galaxy clusters. In this work, we present the properties of UDGs candidates identified through visual inspection around the low-density environment of NGC 3115, the closest S0 galaxy from the Milky Way. We have measured the structural parameters of 41 UDGs candidates using images obtained with the Dark Energy Camera at the Blanco Telescope. Such structural parameters will be used to characterise and select the best UDG candidates, that will have their properties traced for future follow-up campaigns.